A Breast Cancer Clinical Registry in An Italian Comprehensive Cancer Center: An Instrument for Descriptive, Clinical, and Experimental Research. Issue 4 (July 2015) - Baili, Paolo; Torresani, Michele; Agresti, Roberto; Rosito, Giuseppe; Daidone, Maria Grazia; Veneroni, Silvia; Cavallo, Ilaria; Funaro, Francesco; Giunco, Marco; Turco, Alberto; Amash, Hade; Scavo, Antonio; et al.
In clinical research, many potentially useful variables are available via the routine activity of cancer center-based clinical registries (CCCR). We present the experience of the breast cancer clinical registry at Fondazione IRCCS "Istituto Nazionale dei Tumori" to give an example of how a CCCR can be planned, implemented, and used. Five criteria were taken into consideration while planning our CCCR: (a) available clinical and administrative databases ought to be exploited to the maximum extent; (b) open source software should be used; (c) a Web-based interface must be designed; (d) CCCR data must be compatible with population-based cancer registry data; (e) CCCR must be an open system, able to be connected with other data repositories. The amount of work needed for the implementation of a CCCR is inversely linked with the amount of available coded data: the fewer data are available in the input databases as coded variables, the more work will be necessary, for information technology staff, text mining analysis, and registrars (for collecting data from clinical records). A cancer registry in a comprehensive cancer center can be used for several research aspects, such as estimate of the number of cases needed for clinical studies, assessment of biobank specimens with specific characteristics, evaluation of clinical practice and adhesion to clinical guidelines, comparative studies between clinical and population sets of patients, studies on cancer prognosis, and studies on cancer survivorship.